ASPEK RESIDIVIS DAN PEMBERATAN PIDANA PENCURIAN DENGAN PEMBERATAN TERHADAP TINDAK PIDANA DELIK PENCURIAN YANG DILAKUKAN OLEH DARMA SUBUR - Sumiati (The Juris, 2019)
Residual and weighting in criminal offenses for theft causes harm and suffering experienced by victims of crime, this has attracted the attention of the author to examine one of the decisions of the South Jakarta District Court Case Number 538 / Pid.B / 2017 / PN.JKT.Sel. Darma alias Subur was charged with a single indictment of violating Article 363 paragraph (1) of the 4th Criminal Code, prosecuted by the South Jakarta District Prosecutor's Public Prosecutor with a prison sentence of 2 (two) years, and terminated by a Court Judge The land of Muara Bulian with criminal penalties of 9 (nine) months. In the decision the defendant has been proven legally and convincingly guilty of committing "criminal acts of theft in a burdensome state". The defendant's actions were carried out during the day with the destruction of the victim's property. The purpose of the research carried out in the framework of writing in this research is to find out the basis of the consideration of the Judge in bringing criminal charges against the perpetrators of criminal offenses against theft with a weighting against Case Number 538 / Pid.B / 2017 / PN.JKT.Sel. The type of research used in writing this thesis is Normative Jurisdiction, which is to study the laws and regulations relating to the consideration of the judge dropping the criminal against the perpetrator of the crime of theft with the weighting of Case Number 538 / Pid.B / 2017 / PN.JKT.Sel.